AI-Powered Arabic Language Education in the Era of Society 5.0 - Muhammad Rehan Anwar; Herdi Aziz Ahyarudin (Pandawan Sejahtera Indonesia, 2023)
In the Society 5.0 era characterized by technological integration, Arabic language education is experiencing a transformation through the application of artificial intelligence (AI). The background to this research is the increasing need for Arabic language skills amidst globalization and the growth of cross-cultural interactions. Meanwhile, AI technology has reached a level of maturity that allows its effective use in education, providing new opportunities to improve language teaching methods. This research aims to explore the potential of using AI in Arabic language teaching, understanding how this technology can facilitate more adaptive, interactive and efficient learning, according to individual student needs. The implications of this research are very significant. The implementation of AI in Arabic education not only improves language skills, but also enriches students' learning experience. In Society 5.0, where humans and technology synergize, the use of AI in Arabic language education can be a model for integrating intelligent technology in the learning process. The main contribution of this research is the development of an AI learning system that can be adopted by educational institutions, enabling them to provide more personalized and effective Arabic language education. This research also explores updates in teaching methods, introducing an approach based on individual student responses. Thus, this research provides an in-depth understanding of how AI can be adapted to each student's learning needs in the context of Arabic language education. Overall, this research not only provides new insights into the integration of AI in Arabic education, but also provides a foundation for the development of responsive and adaptive curricula in the Society 5.0 era.